Analysis of a Competency Based Curriculum Model to Improve the Quality of Secondary Education in the Era of Globalization - Jeditia Taliak; Gerlan Apriandy Manu; Nurbayani Nurbayani; Hayati Hayati; Fritz Hotman Syahmahita Damanik (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
The primary objective of this study is to analyze a competency-based curriculum model tailored to secondary education, with a specific focus on addressing the challenges and opportunities presented by globalization. This study adopts a qualitative research design, specifically focusing on literature review and library research. Qualitative research is chosen due to its suitability for exploring complex phenomena and gaining in-depth insights into the development of a competency-based curriculum model. The primary sources of data for this study include scholarly articles, books, reports, and other relevant publications related to competency-based education, curriculum development, and secondary education in the era of globalization. The results of this research indicate that the competency-based curriculum model represents a pivotal step towards enhancing the quality of secondary education in the era of globalization. Through a comprehensive analysis of key competencies essential for success in today's interconnected world, including critical thinking, communication, collaboration, creativity, digital literacy, intercultural competence, and adaptability, this study underscores the importance of integrating these competencies into the curriculum framework.